Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Educaplay dalam Meningkatkan Kemampuan Berpikir Kreatif dan Hasil Belajar Siswa - Ainy Pebriani; Herliani; Jailani; Suparno Putera Makkadafi (PendIPA Journal of Science Education, 2026)
This study was motivated by the low levels of creative thinking skills and academic achievement among students during instruction, which resulted in students’ limited understanding of the material and, consequently, low levels of creative thinking skills and academic achievement. This study aims to determine the effect of the Problem-Based Learning model, supported by Educaplay media, on improving the creative thinking skills and learning outcomes of seventh-grade students at SMP Negeri 37 Samarinda. This study employs a quantitative approach with a Nonequivalent Control Group Design. The population for this study consists of all seventh-grade students at SMP Negeri 37 Samarinda. The sampling technique used in this study was purposive sampling. The sample consisted of students in Class VII-C as the experimental group and Class VII-A as the control group. The research instruments included tests to measure students’ creative thinking skills and learning outcomes. Data analysis techniques included normality tests, homogeneity tests, hypothesis testing, and n-gain tests. Based on the results of the data analysis, it was found that the independent samples t-test -test for the Problem-Based Learning model supported by Educaplay media in improving creative thinking skills showed a significance value (0.000 < 0.05), and student learning outcomes also showed a significance value (0.000 < 0.05). Therefore, it can be concluded that the Problem-Based Learning model supported by Educaplay media has an effect on improving the creative thinking skills and learning outcomes of seventh-grade students at SMP Negeri 37 Samarinda.